A Novel Aeromonas popoffii Phage AerP_220 Proposed to Be a Member of a New Tolavirus Genus in the Autographiviridae Family - Morozova, Vera; Kozlova, Yuliya; Jdeed, Ghadeer; Tikunov, Artem; Ushakova, Tatyana; Bardasheva, Alevtina; Zhirakovskaia, Elena; Poletaeva, Yuliya; Ryabchikova, Elena; Tikunova, Nina V. (Viruses, 2022)
Aeromonas popoffii is one of the environmental Aeromonas species. A number of factors of virulence have been described for this species and it has been reported as a causative agent of urinary tract infection. The first A. popoffii bacteriophage AerP_220 along with its host strain A. popoffii CEMTC 4062 were isolated from river water. The phage has a podovirus morphotype, shows a narrow host range and is lytic against the host strain. The AerP_220 genome comprises 45,207 bp and does not contain genes responsible for antibiotic resistance and toxin production. Fifty-nine co-directional putative ORFs were found in the AerP_220 genome. Thirty-three ORFs encoded proteins with predicted functions; the products of 26 ORFs were hypothetical proteins. AerP_220 genome analysis revealed that this phage can be considered a novel species within the Autographiviridae family. Comparative genomic and proteomic analysis revealed that AerP_220 along with the Aeromonas phage vB_AspA_Tola (OM913599) are members of a new putative Tolavirus genus in the family Autographiviridae. The Gajwadongvirus and proposed Tolavirus genera along with Pantoea phage Nufs112 and phage Reminis could form a new Tolavirinae subfamily within the Autographiviridae family.